Physicochemical Characterization of Lignin Recovered from Agriculture and Forestry Biomass - Logambigai, Perichiappan (IRC, 2016)
Agricultural and forestry biomasses are being let as waste materials even though they could provide many useful raw materials for green technology and bio-rooted industry. The purpose of this project is to extract lignin from paddy and rubber wastes and analyze the physical and chemical properties of lignin that can be further used in many other useful application. Two different methods of lignin isolation are used to conduct this study: hydrogen peroxide-treatment and organic extraction method. Paddy wastes such as rice straw and rice husk are dewaxed using sodium hydroxide, NaOH and treated with hydrogen peroxide, H₂O₂. Then, it will be neutralized with hydrochloric acid, HCl and precipitated with ethanol to obtain pure lignin. In terms of rubber waste, rubber wood samples are extracted using dichloromethane (DCM). The extractive free wood is treated with sulfuric acid, H₂SO₄ and go through hydrolysis to attain Klason lignin.